Legal Standing of Coastal Reclamation: Islamic and Positive Law Perspectives - Supriadi Supriadi (Faculty of Law, Hasanuddin University, 2016)
In several regions, the implementation of reclamation in Indonesia caused much conflict. At least, it caused by three interests; the interest of the government, employers, and society (fishermen). The interests of the Government and local authorities to give permission to reclaiming for the pursuit of local revenue, the interests of employers to reclaiming the coastal, because they wanted to add company’s revenues, while the interests of society (fishermen) to defend coastal areas so it not diminish their livelihood. Reclamation in Indonesia has been governed by legislation, but it has not been able to resolve the coastal reclamation. This is due to the legislation governing coastal reclamation, and local governments are ignorant of the rules concerned. In addition, the central and local governments are often tends to interest of employers rather than the fishing communities, so it triggering conflict in reclamation. Positive law as a law made by the government and legislative assembly and the local government with local legislative, a rule that was born as result of an agreement between them, and neglecting the Islamic law that was created by God to organize all the things in this world, including in the management of the universe (coastal). God as the creator of this universe, allowing to manage and utilize natural, if for the benefit of humanity as a whole, and not for those of a human. Therefore, in the implementation of reclamation, the Government and local authorities need to synergize Islamic law into positive law in resolving the problems of social and natural resources.